Diversity patterns and drivers of methanotrophic gene distributions in forest soils across a large latitudinal gradient. Issue 10 (23rd July 2021) - Kou, Yongping; Zhao, Wenqiang; Liu, Yanjiao; Wu, Yanhong; Xiao, Jiangtao; Wang, Xiaohu; Bing, Haijian; Liu, Qing
Abstract: Aim: Methane oxidation driven by soil aerobic methanotrophs exhibits the largest methane sink capacity in forest ecosystems and plays important roles in the alleviation of global warming. Many studies have revealed the distribution of methanotrophs in forest ecosystems at field scales; however, the biogeographical patterns of methanotrophic communities and related ecological processes and the drivers shaping methanotrophic communities at a large scale remain poorly understood. Location: China's forests. Time period: 2012–2013. Major taxa studied: Methanotrophic communities. Methods: We evaluated the geographical distributions of soil methanotrophic communities across 26 forests along a 4, 000‐km north–south transect in China using a MiSeq high‐throughput sequencing technique. The assembly processes and drivers of the methanotrophic communities were evaluated using the phylogenetic null model approach and structural equation modelling, respectively. Results: The results showed that the upland soil cluster α (USCα) and ammonia‐ oxidizing bacteria‐related (AOB‐rel) methanotrophs were the most abundant taxa in forest soils and exhibited contrasting distributions of relative abundance across different climate zones, suggesting that they occupy different environmental niches. The α ‐diversity pattern of the soil methanotrophic community followed a hump‐shaped pattern along a large latitudinal gradient. Statistical analyses suggest that aridity and vegetation productivity [here represented with the normalized difference vegetation index (NDVI)] are major drivers of the α‐diversity of the methanotrophic community, whereas soil pH is the key environmental factor shaping the β‐diversity of the methanotrophic community at a large scale. Additionally, the community assembly of the methanotrophs primarily resulted from deterministic processes, among which heterogeneous selection had a greater contribution in shaping the methanotrophic community than homogeneous selection. Main conclusions: Our study provides new insights into the biogeographical distributions, assembly processes and ecological predictors of the methanotrophic community in forest soil at a large scale. These results can be used to improve simulation models for the better prediction of ecosystem functions under predicted global changes.